Effect of Eating Glutinous Brown Rice Twice a Day for 6 Weeks on Serum 1,5-Anhydroglucitol in Japanese Subjects without Diabetes - Taiga Nakayama; Yoshio Nagai; Yuka Yasunaka; Takeo Uraguchi; Yukihisa Wada; Masakatsu Sone; Yasushi Tanaka (Journal of Nutrition and Metabolism)
We have previously demonstrated that eating glutinous brown rice (GBR) for 1 day or 8 weeks was well accepted and improved glycemic control in patients with type 2 diabetes. The present study evaluated whether eating GBR could also improve glucose metabolism in subjects without diabetes. A prospective 6-week, single-center, randomized, open-label, parallel-group study was carried out in subjects receiving annual medical checkup at our hospital. A total of 42 subjects were randomly assigned to continue their regular diet (RD group) or to switch GBR twice a day (GBR group). The primary outcome was the change in the serum concentration of 1,5-anhydroglucitol (1,5-AG) from baseline after the 6-week dietary intervention. One subject was excluded from the analysis because of a traffic accident. After 6 weeks, the serum 1,5-AG was significantly increased in the GBR group and the mean treatment difference (GBR group − RD group) was 1.1 µg/mL (95% CI: 0.6 to 1.6, p=0.022). Body mass index decreased significantly in both groups, with no significant difference between them (p=0.210). There were no changes in fasting plasma glucose, fasting insulin, or eating behavior. Intake of GBR for 6 weeks significantly increased serum 1,5-AG in Japanese subjects without diabetes. The increase of 1,5-AG may have been due to the alleviation of postprandial hyperglycemia, which could be effective for the primary prevention of diabetes.